Phylogenetic networks : concepts, algorithms and applications - Huson, Daniel H.; Rupp, Regula; Scornavacca, Celine (Cambridge : Cambridge University Press, 2011)
'The evolutionary history of species is traditionally represented using a rooted phylogenetic tree. However, when reticulate events such as hybridization, horizontal gene transfer or recombination are believed to be involved, phylogenetic networks that can accommodate non-treelike evolution have an important role to play. This book provides the first interdisciplinary overview of phylogenetic networks. Beginning with a concise introduction to both phylogenetic trees and phylogenetic networks, the fundamental concepts and results are then presented for both rooted and unrooted phylogenetic networks. Current approaches and algorithms available for computing phylogenetic networks from different types of datasets are then discussed, accompanied by examples of their application to real biological datasets. The book also summarises the algorithms used for drawing phylogenetic networks, along with the existing software for their computation and evaluation. All datasets, examples and other additional information and links are available from the book's companion website at www.phylogenetic-networks.org'--
'In the first part of this book we give an introduction to basic concepts from graph theory and systematics (Chapter 1). We briefly discuss the problem of aligning molecular sequences (Chapter 2) and give a more detailed introduction to the computation of phylogenetic trees from aligned sequences and distances (Chapter 3). Finally, we give a brief introduction to the computation of phyloge-netic networks, which also serves as an overview for the material presented in the second and third parts of the book (Chapter 4). Chapters 2 and 3 are provided for the sake of completeness and reference. They can be skipped by readers who have a basic knowledge of phylogenetic'--
Includes bibliographical references and index.
Keywords: Cladistic analysis -- Data processing; Cladistic analysis -- Mathematics; Phylogeny